Not coped with by a machine: on Frege's conception of logic as science - Schmidt , João Vitor (Revista Ética e Filosofia Política, 2023)
Following logicism, Frege famously held that logic is a science on its own. Particularly, he held the informativity thesis, viz., that logic is a science because it is deductively informative. This paper aims to understand Frege’s informativity thesis and its connection with the conception of logic as science. For such, it focuses on some features of Frege’s philosophy that are key for understanding this connection, particularly his conception of analyticity, the role of judgments in inferential reasoning, and the use of decomposition of functions as a means for concept-formation, which Frege names as fruitful definitions. Keywords: Gottlob Frege; Informativity of Logic; Judgements; Fruitful Definitions.